Caregiver burden of carers of children with cerebral palsy in selected hospitals, Southwestern Nigeria - Oluwasola Adetola Solaja; Adenike A. Olaogun (BMC Nursing)
Abstract Background Caring for children with Cerebral Palsy (CP) placed a heavy burden on the carers, which usually affects different aspects of the life of the carers. Knowledge of their burden helps to inform the broad assessment of caregivers’ burden, leading to the development of a client-oriented nursing care plan capable of delivering holistic care. This plan can also inform the development of educational packages, institutional care practices, and a structured support group system that addresses the core challenges of carers of children with CP in third-world countries. Thus, this study assessed the caregiver burden of caregivers of children with cerebral palsy (CP) in southwestern Nigeria. Methods This study used a concurrent mixed methods design. The settings of the study were Obafemi Awolowo University Teaching Hospitals Complex (OAUTHC), Ile-Ife, Osun State and Massey Children’s Hospital, Lagos, Lagos State. Samples were determined using the adjusted Cochran formula. A purposive sampling technique was used to select 92carers from the selected hospitals in Southwestern Nigeria for the quantitative part, while twelve carers participated concurrently in the qualitative study. Data was collected with the use of a standardised instrument (Zarit Burden Interview) and an interview guide for the In-depth interview. Quantitative data analysis was done using the Statistical Product and Service Solutions (SPSS) version 23, while the qualitative data were analysed using content analysis. Hypotheses were tested with an alpha value set at p ≤ 0.05. Results The study found that the majority of carers (91.3%) were between 20 and 50 years, over 89% were females, married (91.3%), mothers (81.5%), with tertiary (47.7%) and senior secondary (35.9%) education. Nearly half of the carers were employed (46.7%), and 40.2% of them were self-employed. The results showed that nearly half of the carers (42.4%) had a moderate burden, 31.5% had a mild burden, while 15.2% had a severe burden. The qualitative data identified the burden as physical stress, time constraint, lack of support, emotional burden, and financial and economic burden. There was a significant association between the educational level of carers (χ2 = 18.39, p = 0.03), the occupation of carers (χ2 = 12.36, p = 0.05), and caregiver burden. Conclusion This study concluded that about half of the carers experienced moderate caregiver burden.